2004
DOI: 10.1103/physrevlett.92.223002
|View full text |Cite
|
Sign up to set email alerts
|

Nearest-Neighbor-Atom Core-Hole Transfer in Isolated Molecules

Abstract: A new phenomenon sensitive only to next-door-neighbor atoms in isolated molecules is demonstrated using angle-resolved photoemission of site-selective core electrons. Evidence for this interatomic coreto-core electron interaction is observable only by measuring nondipolar angular distributions of photoelectrons. In essence, the phenomenon acts as a very fine atomic-scale sensor of nearest-neighbor elemental identity. DOI: 10.1103/PhysRevLett.92.223002 PACS numbers: 33.60.Fy, 33.80.Eh For decades, photoelec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 18 publications
2
12
1
Order By: Relevance
“…The same nearest-neighbor Q-NACHT effect was observed (Guillemin et al, 2004). The same nearest-neighbor Q-NACHT effect was observed (Guillemin et al, 2004).…”
Section: Nearest-neighbor Atom Core-hole Transfersupporting
confidence: 73%
See 1 more Smart Citation
“…The same nearest-neighbor Q-NACHT effect was observed (Guillemin et al, 2004). The same nearest-neighbor Q-NACHT effect was observed (Guillemin et al, 2004).…”
Section: Nearest-neighbor Atom Core-hole Transfersupporting
confidence: 73%
“…To search for NACHT effects, direct photoemission from the two inequivalent N 1s core levels in N 2 O was probed in the vicinity of the resonant excitation of an O 1s electron to the lowest unoccupied 3p n molecular orbital (Guillemin et al, 2004). The O 1s ionization threshold lies about 130 eV above the nitrogen thresholds, at 541.4 eV.…”
Section: Nearest-neighbor Atom Core-hole Transfermentioning
confidence: 99%
“…Therefore, we could not find any signature of the IARA effect in the LF-PADs. In addition, there was no significant difference in the non-dipole parameters between on-and off-resonant LF-PADs, whilst non-dipolar angular distributions of core-level photoemissions were a measure of the IARA in the free N 2 O and OCS molecules [19]. In contrast to this, the geometrydependent MF-PADs, or equivalently the symmetry selected MF-PADs, can provide the direct evidence of the IARA, as reported in our previous paper [20].…”
Section: Coincidence Velocity Map Imaging Spectroscopymentioning
confidence: 90%
“…One promising approach to observing such an interatomic effect is differential crosssection measurements which provide detailed information about photoionization dynamics. The first attempt to observe the IARA in isolated molecules has been made by measuring the nondipole contributions of core-level photoelectrons from free N 2 O and OCS molecules [19]. Later, a fixed-molecule experiment based on photoelectron-fragment-ion-fragmention coincidence momentum spectroscopy was applied to the IARA of NO [20], which found that the molecular frame N 1s photoelectron angular distributions (PADs) are slightly affected by the O 1s → π * resonance.…”
Section: Introductionmentioning
confidence: 99%
“…However, this study underestimates the relative intensity of such effects in considering the squares of the direct and resonant matrix elements involved, rather than the matrix elements themselves, since it is the interference between the two processes that leads to MARPE 4,10 . Finally, more subtle effects on the non-dipole angular distributions parameters in core emission from small gasphase molecules have been observed, in particular for N 1s emission from N 2 O with two inequivalent N atoms as the O 1s resonance is scanned, and C 1s and S 2p emission from OCS, again as the O 1s resonance is scanned 18 . These effects have been termed near-atom core-hole transfer (NACHT), but they also represent a manifestation of MARPE, albeit a more subtle one.…”
Section: Introductionmentioning
confidence: 99%